(untitled) (diségno, 2021)
In 2007, OFFICE Kersten Geers David Van Severen presented the project OFFICE 37 – A Green Archipelago, a dwelling prototype involving four forests with their respective settlement systems on the artificial Marker lake in Holland. The four forests were represented as islands (or barges) occupied by a dense mesh of trees in parallel rows and at a distance of 10 meters from each other. Within the forest a system of partitions, parallel to the dispositio of the plants, replicates the structure and articulation, translating the materials and thus determining the spaces for the human settlement in the form of a variation of a courtyard-house; vast voids interrupt the anthropic and plant mesh, deriving into two compositional possibilities, both based on subtraction: settlement along the fringes and central settlement, accommodating in this way collective functions, all indicated with the comprehensive term ‘care’, theoretical variation of the space for’ curing’ (care/cure). The representation through a mutually reciprocal rationale of the spaces (black-exterior, white-interior) generates a shift in the reported signifiers, declaring by way of a series of images that are preliminary to the project, of collages which become true and proper tools within the process, to already be on a journey: the ‘controlled hallucinations’ are the results of the inquiry concerning both ‘sensation’ and ‘perception’. OFFICE has imagined another galaxy, one nearby, the one next to us.